2002
DOI: 10.1038/nature01118
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of voltage-gated calcium channels by PtdIns(4,5)P2

Abstract: Voltage-gated calcium channels (VGCCs) conduct calcium into cells after membrane depolarization and are vital for diverse biological events. They are regulated by various signalling pathways, which has profound functional consequences. The activity of VGCCs decreases with time in whole-cell and inside-out patch-clamp recordings. This rundown reflects persistent intrinsic modulation of VGCCs in intact cells. Although several mechanisms have been reported to contribute to rundown of L-type channels, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
257
3
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(273 citation statements)
references
References 29 publications
11
257
3
2
Order By: Relevance
“…The dual effect of PIP 2 on voltage sensitivity and on the stability of the open state also has been shown for voltage-gated Nand P/Q-type Ca 2+ channels (32). Although currently untested, it is possible that the S4-S5 linker of Ca v channels, as in Kv channels, is critically involved in mediating the effects of PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The dual effect of PIP 2 on voltage sensitivity and on the stability of the open state also has been shown for voltage-gated Nand P/Q-type Ca 2+ channels (32). Although currently untested, it is possible that the S4-S5 linker of Ca v channels, as in Kv channels, is critically involved in mediating the effects of PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…SCG neurons were studied under perforated patch whole-cell voltage clamp and were pretreated with the G o/i blocker, pertussis toxin, to isolate G q/11 -mediated actions (42). Our previous work reported suppression of I Ca by muscarinic M 1 receptors, but not bradykinin B 2 or purinergic P2Y receptors, via depletion of PIP 2 molecules in the membrane, which are necessary for Ca 2ϩ channel activity (10,11,14). Thus, the Ca 2ϩ channels act as a PIP 2 biosensor, and depression of I Ca reports depletion of PIP 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the I Ca in these cells makes an ideal biosensor of PIP 2 depletion by receptors, similar to the reporting by highly PIP 2 -sensitive GIRK K ϩ channels when expressed in the same neurons (9). It is important to note that such dramatic receptor specificity is only seen in native cells (23,(62)(63)(64)(65)(66)(67) and is wholly absent in reconstituted systems in which channels and receptors are heterologously expressed, in which all PLC-linked receptors elicit large Ca 2ϩ i signals and all probably work similarly (8,11,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Hilgemann and Ball (12) revealed for the first time that the Na ϩ /Ca 2ϩ exchanger and ATP-sensitive K ϩ channels are positively regulated by endogenous PtdIns(4,5)P 2 in guinea pig cardiac cell membranes. Recent studies have demonstrated that PtdIns(4,5)P 2 modulates the function of a number of ion channels, including many inwardly rectifying K ϩ channels (13)(14)(15), the HERG K ϩ channel (16) and voltage-gated P/Q-type Ca 2ϩ channels (17).…”
mentioning
confidence: 99%